2012
DOI: 10.1124/mol.112.079889
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characteristics of CTA056, a Novel Interleukin-2-Inducible T-Cell Kinase Inhibitor that Selectively Targets Malignant T Cells and Modulates Oncomirs

Abstract: Interleukin-2-inducible T-cell kinase (Itk) is a member of the Btk (Bruton's tyrosine kinase) family of tyrosine kinases. Itk plays an important role in normal T-cell functions and in the pathophysiology of both autoimmune diseases and T-cell malignancies. Here, we describe the initial characterization of a selective inhibitor, 7-benzyl-1-(3-(piperidin-1-yl)propyl)-2-(4-(pyridin-4-yl)phenyl)-1H-imidazo[4,5-g]quinoxalin-6(5H)-one (CTA056), that was developed through screening a 9600-compound combinatorial solut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 49 publications
0
25
0
Order By: Relevance
“…Previous studies about the putative oncogenic role of ITK have been limited to its increased or aberrant expression in T-cell malignancies (42-44). It has also been reported that an ITK inhibitor had cytotoxic effects on malignant T cells (43). We are not aware of previous studies reporting ITK inhibition of solid tumor malignancies.…”
Section: Discussionmentioning
confidence: 93%
“…Previous studies about the putative oncogenic role of ITK have been limited to its increased or aberrant expression in T-cell malignancies (42-44). It has also been reported that an ITK inhibitor had cytotoxic effects on malignant T cells (43). We are not aware of previous studies reporting ITK inhibition of solid tumor malignancies.…”
Section: Discussionmentioning
confidence: 93%
“…CTA056, 7-benzyl-1-(3-(piperidin-1-yl)propyl)-2-(4-(pyridin-4-yl)phenyl)-1 H -imidazo[4,5- g ]quinoxalin-6(5 H )-one, was developed through screening a library comprising 9600 compounds, followed by molecular modeling and analysis of SAR [88]. It showed the highest inhibition toward ITK with an IC 50 of 100 nM, followed by BTK with an IC 50 of 400 nM.…”
Section: Itk Inhibitorsmentioning
confidence: 99%
“…4 In cancer, ITK is a critical signaling motif important to acute lymphoblastic T-cell leukemia and Sézary syndrome/cutaneous T-cell lymphoma due to aberrant activation and heightened expression. 5 In healthy Th1-polarized and CD8 effector cells, ITK plays a supportive yet dispensable role to RLK. However, the epigenetic evolution of Th2 cells conserves a singular dominant role for ITK, pinning it as the Achilles' heel of Th2 T cells.…”
Section: Introductionmentioning
confidence: 99%